Systemic lupus erythematosus: causes and manifestations. Issue 1 (27th January 2020) - Barcia‐Sixto, Laura; Isenberg, David
Abstract : Little is known about the precise aetiology of systemic lupus erythematosus, but treatment should be individualised according to predominant symptoms, organ involvement, response to previous therapy and disease activity and severity.